Pengaruh Stres Kerja Terhadap Semangat Kerja Karyawan Pada PT. Kinchay Manokok Indonesia - Dehotman, Khornelis (Eko dan Bisnis: Riau Economic and Business Review, 2025)
This research was carried out at PT Kinchay Manokok Indonesia Soekarno-Hatta branch. The formulation of the research problem is whether workstress has an effect on employee morale at PT Kinchay Manokok Indonesia Soekarno-Hatta branch. The purpose of this research is to determine the effect ofemployee work stress on employee morale at PT Kinchay Manokok Indonesia Soekarno-Hatta branch.This research method is descriptive with a quantitative approach. The population in this study were 38 employees at PT Kinchay Manokok, Soekarno-Hatta branch. The sample in this study was 38 people minus one person, namely management, because it did not include employees, the sample in this study was 37 people. Based on the t test that has been carried out, the results obtained  are a t value of 4.362 while t table is 2.026. This means that the value of t count > t table with a significance level of 0.000<0.005, then Ho is rejected and Ha is accepted and R2 value of 0.352 is obtained. This explains the magnitude of the influence of theemployee work stress variable, employee work morale is 35.2% and the remaining 64.8% is influenced by other variables not examined in this study. From the research results of a simple linear regression test, the equation obtained is Y= 24.023+0.566X.